Model MAtematika Pemekaran Pada Ekstrusi CAmpuran Tepung Ketela Dan Tepung Jagung = Mathematics Model for Expansion of Extrusion Mixing from Cassava and Corn Flours - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Abstract Extrusion of foods was a process in which material entering and flows downs in the screw undergoes elevated pressure and temperature in a short time, to produce a puffed-dry extrudate. This objective of the experiment was to developed mathematics model to determine expansion index as Sectional (SEI), Longitudinal (LEI), and Volumetric (VEI), envelope effect of moisture, melt temperature, shear strain of screw and die including material fraction feeding. Determination of expansion index was initialed with controlling the condition of Single Screw Extruder Brabender type EX 20 DN process that name Refference. The specification of Acuan process including control temperature in feed section 150 °C, compression section 170 °C, and metering section 170 °C, with feeding and screw rotation speeds 80 RPM and 160 RPM respectively. In this process specify screw that used was 1:1. Varieties of process including temperature (160 °C, 180 °C, 180 °C), screw (1:3), and screw rotation speed (180 RPM). All of them were tested for fraction of cassava towards corn flours 0